SYNTHESIS AND EVALUATION OF SULPHONYL BORATE ESTER AS GREASE ADDITIVE - Hassan Elsayed Ali; Mohammed Emad Azab; Nagy Soliman Sakr (Scientific Contributions Oil and Gas, 2023)
This study includes synthesis and evaluation of an additive to improve the two main properties of lubricating grease which are; â€œincreasing the dropping point and improving the extreme pressure (EP) propertiesâ€ of Lithium grease without any negative effect on the other characteristics of lubricating grease. Increasing the dropping point and extreme pressure (EP) properties are the most important factors to widen the application of lubricating grease. The additive is synthesized via two-steps condensation reactions of polyethylene glycol 400 and Boric acid followed by reacting the product with Dodecyl-benzene sulfonic acid in the presence of Xylene as azeotropic solvent. The structure of the synthesized Sulphonyl-Borate ester SPB is confirmed by using FT-IR. Evaluation of the synthesized additive is conducted by blending it with laboratory prepared Lithium grease sample in different ratios. Analysis were carried out to study the effect of additive on the lubricating grease properties, especialy grease consistency ASTM D217, dropping point ASTM D2265, oil separation ASTM D6184, and Fourâ€“Ball test ASTM D2783. The results showed that synthesized additive increased the dropping point by 65 % and extreme pressure properties by 66 % of the prepared grease grease sample.